Blackberry (Rubus fruticosus L.) Fruit Extract Phytochemical Profile, Antioxidant Properties, Column Chromatographic Fractionation, and High-performance Liquid Chromatography Analysis of Phenolic Compounds - Qader, Aryan F.; Yaman, Mehmet (Koya Univ, 2023)
This groundbreaking study explores the untapped potential of blackberries, a member of the Rubus genus in the Rosaceae family, and sheds light on their remarkable health and medicinal properties. Unlike previous research conducted in other regions, this investigation focuses specifically on the blackberry fruit's phytochemical constituents, chromatographic fractionations, and antioxidant activities in the Koisinjaq and Erbil villages of Northern Iraq. The research unveils seven distinct fractions obtained through column chromatography, with Fractions 2 and 3,5 found to contain p-coumaric acid and rutin, respectively, while Fraction 2 also houses chlorogenic acid. The analysis reveals the impressive richness of the methanolic blackberry extract in phenolic content (38.08 mg gallic acid equivalent/g dry weight [DW]), flavonoids (14.58 mg quercetin equivalent/g DW), flavonols (6.95 mg rutin equivalent/g DW), and anthocyanins (7.73 mg/kg DW), underlining the fruit's potent antioxidant activity. Furthermore, blackberries display exceptional ferric-reduction and metal-chelating capabilities, with 20.53 mg FeSO4/g and 182.12 mg Fe2(+)/g DW, respectively. Remarkably, blackberries also exhibit a remarkable ability to inhibit amylase activity (76.01% ). These findings open up exciting prospects for utilizing blackberry fruit as a natural and potent source of phytochemicals and antioxidants in the food and pharmaceutical industries, promising transformative applications in health and well-being.
Keywords: Rubus fruticosusm; Phytochemical; Antioxidants; Column chromatography; Phenolic